Measuring and Analyzing the Impact of Residential Investment on the Number of Tenants in the Kurdistan Region - علي عبدالله, بابان; علي أحمد, يونس (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
Investment in Shelter forms a cornerstone of the contemporary economic structure, The emphasis is on creating housing developments to address the rising need for homes and to generate rapid and valuable economic returns. In return, tenants are the main driver of economic returns in this sector and the main motivation for investment in the housing sector. This study attempts to explain how housing investment in the Kurdistan Region has affected the decline in occupancy rates by analyzing actual housing investment, occupancy degrees, and how they are interconnected. The study relied on descriptive analysis and standard approaches and used the ARDL model with short and long term variables (housing investment, occupancy rate, personal income, family formation, population, and unemployment rate) for the study over the period (2006-2024) incorporating a dummy variable representing the war against the terrorist organization. A 1% increase in housing investment decreases the occupancy rate by 0.0115% in the near term and 0.0257% in the long term. This reflects an inverse relationship between housing investment and occupancy, consistent with economic theory and previous studies. It also suggests that the impact of investment in real estate The decrease in occupancy aligns with the current situation in the Kurdistan region, although not at the required level. Furthermore, all other independent variables are significant and influential, albeit at different levels. The study makes several recommendations, including the need to organize and support housing investments in order to build housing within purchasing power and to contribute more effectively to occupancy reduction. It also emphasizes the importance of granting real estate loans to tenants through land distribution and long-term installment payments.